EVALUATION OF POLICIES ON THE FIT AND PROPER TEST FOR STRATEGIC OFFICIALS IN SUPPORTING EFFORTS TO PREVENT AND ERADICATE CORRUPTION - Budi Saiful Haris (Association of Certified Fraud Examiners Indonesia Chapter, 2019)
Integrity of strategic officials is absolutely necessary to support the effective implementation of corruption prevention and eradication system in a government. To get officials with integrity, one of the efforts pursued is to apply the mechanism of fit and proper test. Based on a comparative study of various invitation laws, it was found a number of crucial issues relating to the policy of the fit and proper test of a number of strategic officials. These crucial issues include differences in the standard requirements of prospective officials, the presence / absence of a selection committee, the absence of detailed guidelines on information sources and measures to provide objective assessments of the value of integrity from a candidate, and provisions regarding dismissal of officials who are potentially counterproductive with corruption prevention and eradication efforts